Brain activation display functional asymmetry in response to action, background and tonal frequency during a pitch memory processing: an fMRI study - Ahmad Nazlim Yusoff,; Khairiah Abdul Hamid,; Farah Nabila Ab Rahman,; Mazlyfarina Mohamad,; Siti Zamratol-Mai Sarah Mukari, (Penerbit Universiti Kebangsaan Malaysia, 2018)
In this study, the asymmetry of the main effects of action, background and tonal frequency during a pitch memory processing were investigated by means of brain activation. Eighteen participants (mean age 27.6 years) were presented with low and high frequency tones in quiet and in noise. They listen, discriminate and recognize the target tone against the final tone in a series of four distracting tones. The main effects were studied using the analysis of variance (ANOVA) with action (to wring (rubber bulb) vs. not to wring), background (in quiet vs. in noise) and frequency (low vs. high) as the factors (and levels respectively). The main effect of action is in the right pre-central gyrus (PCG), in conformation with its contralateral behavior. The main effect of background indicated the bilateral primary auditory cortices (PAC) and is right lateralized, attributable to white noise. The main effect of frequency is also observed in PAC but bilaterally equal and attributable to low frequency tones. Despite the argument that the temporo-spectral lateralization dichotomy is not especially rigid as revealed by the main effect of frequency, right lateralization of PAC for the respective main effect of background clearly demonstrates its functional asymmetry suggesting different perceptual functionality of the right and left PAC.